Fabulous paper airplanes - Churchill, E. Richard (Sterling Publishing Co., Inc. New York, 1991)
Explains the basic principles of flight and gives folding instructions for twenty-nine paper airplanes.
Includes index.
Keywords: Paper airplanes; Handicraft; Paper airplanes -- Juvenile literature